The Chukchi Personal Song of north-eastern Siberia as a turning point in musical thought - Siirala, Pia (Trio, 2024)
Becoming acquainted with the music of the indigenous people of north-eastern Siberia has been a turning point in my perception of music, and has made me question what music is at a fundamental level. In my fieldtrips to north-eastern Siberia I studied the music of the Chukchi and other indigenous peoples. This doctoral project centred on my particular interest in the Chukchi Personal Song, in which music is part of their persona. Tutustuminen koillisen Siperian alkuperäiskansojen musiikkiin on ollut koko musiikillisen ajatteluni käännekohta, joka on kyseenalaistanut ymmärrystäni musiikista. Kenttämatkoillani koilliseen Siperiaan tutkin tšuktšien ja muiden alkuperäiskansojen musiikkia. Mielenkiintoni herätti erityisesti tšuktšien henkilölaulu, joka kuuluu arktisten alkuperäiskansojen kulttuuriperinteeseen, jossa musiikki on osa heidän persoonaansa.